Pengaruh Media Sosial Instagram @wonderfulindonesia Terhadap Citra Destinasi Indonesia - Dellia Paramitha; Indria Angga Dianita (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
Instagram social media is a digital application that is used to be able to provide information and carry out two-way communication with fellow users. In Instagram, there are features that can be used to support communication, including hashtags, geotags, follow, share, like, comments, mentions. The purpose of this study was to determine the influence of social media Instagram @wonderfulindonesia on the image of Indonesian destinations. The method used in this study is quantitative with the correlation coefficient test and the coefficient of determination test and the data analysis technique uses simple linear regression analysis. The results of the correlation coefficient test were 0.895 so that it can be concluded that Instagram social media variables and destination image variables have a very strong relationship. In addition, it was found that there was a relationship between Instagram social media variables that affected the image of Indonesian destinations by 80%, while 20% were influenced by other variables not discussed in this study. The positive and significant influence on the image of the Indonesian destination, as evidenced by the results of a simple linear regression of 0.611 on the Instagram social media variable has the effect that every one unit increase will affect the Indonesian destination image variable.